Heterojunction catalytic material and preparation method and application thereof

By forming heterojunction catalytic materials of Fe2O3 and BiVO4 nanorods on the conductive substrate, the problems of slow kinetics and low carrier mobility in photoelectrochemical water decomposition are solved, and efficient photoelectrolytic hydrogen production is achieved, which simplifies the The preparation process and the photoelectric hydrogen production efficiency are improved.

CN119287425APending Publication Date: 2025-01-10WUYI UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411371308.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

In the existing photoelectrochemical water decomposition technology, the photoanode has the problem of rapid recombination of surface charges and slow oxidation reaction kinetics, resulting in slow kinetics and low carrier mobility, making it difficult to achieve efficient water decomposition.

Method used

Type II heterojunction catalytic material of Fe2O3 and BiVO4 nanorods formed on the conductive substrate is prepared by two-step electrochemical deposition method to improve the efficiency of electron transmission kinematics and photoelectric hydrogen production.

Benefits of technology

It realizes efficient photoelectric hydrolysis and hydrogen production, improves the photoelectric hydrogen production efficiency, simplifies the preparation process, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119287425A_ABST
    Figure CN119287425A_ABST
Patent Text Reader

Abstract

The invention discloses a heterojunction catalytic material as well as a preparation method and application thereof. The heterojunction catalytic material comprises a conductive substrate, a BiVO4 nanorod and Fe2O3, wherein the BiVO4 nanorod is arranged on the conductive substrate; the BiVO4 nanorod is positioned on the surface of the substrate; the Fe2O3 nanorod and the BiVO4 nanorod form a heterojunction; and the Fe2O3 is distributed on the BiVO4 nanorod. The heterojunction catalytic material has relatively high electron transport kinematics, and can realize photoelectric hydrolysis hydrogen production; and the photoelectric hydrogen production efficiency is relatively high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of photoelectric catalysis technology, and in particular to a heterojunction catalytic material and a preparation method and application thereof. Background Art

[0002] With the progress of science and technology and social development, energy problems are increasingly exposed to people. The environmental and energy reserve problems brought about by traditional non-renewable energy such as coal, oil and natural gas are becoming more and more serious. Therefore, the research on new renewable green energy is becoming more and more important. As an environmental energy source, the demand for establishing efficient and high-performance hydrogen production catalytic systems is growing. Photoelectrochemical (PEC) water splitting has become a promising solution due to its sustainability and efficiency. Photoelectrochemical PEC is a technology that uses photoanode materials to absorb light energy, and the electrons and holes on the surface participate in the redox reaction of water decomposition oxygen and hydrogen evolution to achieve energy conversion. However, the photoanode involves the reaction 2H2O→O2+4H+4e in the process of water splitting, with slow kinetics, short pore diffusion length and low carrier mobility, and severe hole recombination, which makes the research of photoanode more challenging and difficult.

[0003] The photoanode in the related art has problems such as rapid recombination of surface charges and slow oxidation reaction kinetics, which requires additional bias to promote charge transfer. Therefore, in order to achieve efficient photoelectrochemical water splitting, it is necessary to develop a new type of catalytic material for photoelectrochemical water splitting. Summary of the invention

[0004] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the first aspect of the present invention provides a heterojunction catalytic material, which has high electron transport kinetics when used for photoelectrochemical water decomposition, can realize photoelectrochemical water decomposition to produce hydrogen, and has high photoelectrochemical hydrogen production efficiency.

[0005] The second aspect of the present invention also provides a method for preparing a heterojunction catalytic material.

[0006] The third aspect of the present invention also provides an application of a heterojunction catalytic material.

[0007] According to the first aspect of the present invention, a heterojunction catalytic material is provided, comprising a conductive substrate, BiVO4 nanorods and Fe2O3; the BiVO4 nanorods are located on the surface of the substrate; the Fe2O3 and the BiVO4 nanorods form a heterojunction; and the Fe2O3 is distributed on the BiVO4 nanorods.

[0008] The heterojunction catalytic material according to the embodiment of the present invention has at least the following beneficial effects:

[0009] The invention forms a type II heterojunction with Fe2O3 and BiVO4 nanorods on the surface of a conductive substrate; the heterojunction catalytic material has high electron transport kinetics, can realize photoelectric hydrolysis to produce hydrogen, and has high photoelectric hydrogen production efficiency.

[0010] According to a preferred embodiment of the present invention, the particle size of the BiVO4 nanorods is 150-300 nm.

[0011] According to a preferred embodiment of the present invention, the particle size of the heterojunction is 250-400 nm.

[0012] According to a preferred embodiment of the present invention, the sheet resistance of the conductive substrate is ≤15Ω.

[0013] According to a preferred embodiment of the present invention, the conductive substrate is selected from at least one of FTO conductive glass and Si substrate.

[0014] According to a second aspect of the present invention, there is provided a method for preparing the heterojunction catalytic material according to the first aspect of the present invention, comprising the following steps:

[0015] S1, using bismuth salt solution, potassium iodide solution and benzoquinone solution as electrolyte I, using conductive substrate as working electrode, and using electrochemical method to deposit I; mixing the working electrode and vanadium acetylacetonate solution and annealing I to obtain BiVO4 nanorod electrode;

[0016] S2. Using a mixed solution of potassium chloride solution, potassium fluoride solution, ferric chloride solution and hydrogen peroxide solution as electrolyte II, using the BiVO4 nanorod electrode in step S1 as the working electrode, electrochemically depositing II and annealing II to obtain a heterojunction catalytic material.

[0017] Therefore, the preparation method of the present invention can be obtained by a two-step electrochemical deposition method, the method is relatively simple, and can be used for large-scale preparation.

[0018] According to a preferred embodiment of the present invention, the temperature of the annealing I is 400-700°C.

[0019] According to a preferred embodiment of the present invention, the annealing time I is 0.5 to 5 hours.

[0020] According to a preferred embodiment of the present invention, the temperature of the annealing II is 550-750°C.

[0021] According to a preferred embodiment of the present invention, the annealing II takes 1 to 3 hours.

[0022] According to a preferred embodiment of the present invention, in step S1, the concentration of the bismuth salt solution is 3-5 mM, the concentration of the potassium iodide solution is 0.3-0.6 M, and the concentration of the benzoquinone solution is 0.1-0.4 M.

[0023] According to a preferred embodiment of the present invention, in step S2, the concentration of the potassium chloride solution is 0.05-0.15M, the concentration of the potassium fluoride solution is 0.02-0.07M, the concentration of the ferric chloride solution is 0.02-0.06M, and the concentration of the hydrogen peroxide solution is 0.5-1.5M.

[0024] According to a preferred embodiment of the present invention, the concentration of the vanadium acetylacetonate solution is 0.1-0.4M.

[0025] According to a preferred embodiment of the present invention, the voltage of the deposition I is -0.12 to -0.1 V vs. Ag / AgCl.

[0026] According to a preferred embodiment of the present invention, the voltage of the deposition II is -2.0V to 0.5V vs. Ag / AgCl.

[0027] According to a preferred embodiment of the present invention, the voltage of the deposition II is -0.15V to 0.5V vs. Ag / AgCl.

[0028] According to a preferred embodiment of the present invention, in step S1 or step S2, the electrochemical deposition method further includes a counter electrode and a reference electrode.

[0029] According to a preferred embodiment of the present invention, the counter electrode is selected from a Pt wire electrode.

[0030] According to a preferred embodiment of the present invention, the reference electrode is selected from Ag / AgCl electrode.

[0031] The third aspect of the present invention provides an application of the heterojunction catalytic material described in the first aspect of the present invention in a photoelectrocatalytic water decomposition system.

[0032] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be apparent from the description, or may be learned by practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0034] Figure 1 This is a SEM top view of the BiVO4 nanorods in Example 1 of the present invention.

[0035] Figure 2 This is a SEM top view of the heterojunction in Example 1 of the present invention.

[0036] Figure 3 This is a linear scanning curve diagram of the heterojunction catalytic material of Example 1 of the present invention. DETAILED DESCRIPTION

[0037] The following are specific embodiments of the present invention, and the technical solutions of the present invention are further described in conjunction with the embodiments, but the present invention is not limited to these embodiments.

[0038] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0039] Example 1

[0040] This example provides a heterojunction catalytic material, including a conductive substrate, BiVO4 nanorods and Fe2O3; the BiVO4 nanorods are located on the surface of the substrate; the Fe2O3 and the BiVO4 nanorods form a heterojunction; and the Fe2O3 is distributed on the BiVO4 nanorods. The preparation method thereof is as follows:

[0041] Substrate selection: FTO conductive glass (square resistance <15Ω) is used.

[0042] S1. Using electrochemical deposition method, 4mM bismuth nitrate solution, 0.4M potassium iodide and 0.2M benzoquinone solution were used as electrolyte, FTO conductive glass, Pt wire and Ag / AgCl were used as working electrode, counter electrode and reference electrode respectively, and BiOI was deposited on FTO by electroplating at a bias voltage of -0.12V vs.Ag / AgCl for 400s to obtain BiOI; then it was immersed in 0.2M vanadium acetylacetonate solution for 1min, and annealed at 450℃ in oxygen atmosphere for 2h; finally, it was immersed in 1M NaOH solution for 30min to remove V2O5 to obtain BiVO4 nanorods;

[0043] S2. The prepared BiVO4 nanorods were ultrasonically cleaned in ethanol, acetone and water in sequence. Then, the electrochemical deposition method was used, with 0.05M ferric chloride, 0.05M potassium fluoride, 0.1M potassium chloride and 1M hydrogen peroxide solution as electrolyte, BiVO4 nanorods, Pt wire and Ag / AgCl as working electrode, counter electrode and reference electrode respectively, and 15 cycles of electroplating were performed at a bias voltage of -0.10V to 0.5V vs.Ag / AgCl to deposit FeOOH on the BiVO4 nanorods to obtain BiVO4 / Fe3OOH; then the above electrode sheets were annealed at 650℃ in an oxygen atmosphere for 2h; finally, they were rinsed in pure water to obtain heterojunction catalytic materials.

[0044] The BiVO4 nanorods prepared in step S1 of the present invention were subjected to SEM detection, and the results are as follows: Figure 1 As shown, the particle size of BiVO4 nanorods is about 200 nm.

[0045] Furthermore, the heterojunction formed in step S2 of the present invention is subjected to SEM detection, and the result is as follows: Figure 2 As shown, the surface of BiVO4 is covered with a thin film.

[0046] Furthermore, the heterojunction catalytic material prepared in Example 1 of the present invention was used for photoelectrolysis of water. The prepared heterojunction catalytic material was made into a photoelectrode. The photoelectrochemical test was carried out using an electrochemical workstation, as follows: 0.5 mol / L Na2PO4 (PH≈9) solution was used as the electrolyte, the prepared photoelectrode was used as the anode, Ag / AgCl was used as the reference electrode, Pt wire was used as the cathode, and a 300 W Xe lamp (light intensity ~100 mW / cm 2 ) as the light source, and the photocurrent density-bias curve was obtained. The linear scanning curve is shown in Figure 3. When the photoelectrode is biased at 1.2V vs. RHE, the photocurrent density is 0.43mA / cm 2 .

[0047] Example 2

[0048] This example provides a heterojunction catalytic material, comprising a conductive substrate, BiVO4 nanorods and Fe2O3; the BiVO4 nanorods are located on the surface of the substrate; Fe2O3 and the BiVO4 nanorods form a heterojunction; Fe2O3 is distributed on the BiVO4 nanorods, wherein the particle size of the BiVO4 nanorods is about 200nm, and the particle size of the heterojunction is about 300nm. The preparation method thereof comprises the following steps:

[0049] Substrate selection: FTO conductive glass (square resistance <15Ω) is used.

[0050] S1. Electrochemical deposition method was used, with 4 mM bismuth nitrate solution, 0.4 M potassium iodide and 0.2 M benzoquinone solution as electrolyte, FTO, Pt wire and Ag / AgCl as working electrode, counter electrode and reference electrode respectively, and BiOI was deposited on FTO for 400 s at a bias of -0.12 V vs. Ag / AgCl to obtain BiOI; then the above electrode sheets were immersed in 0.2 M vanadium acetylacetonate solution for 1 min, and annealed at 450 ° C in oxygen atmosphere for 2 h; finally, they were immersed in 1 M NaOH solution for 30 min to remove V2O5 to obtain BiVO4 nanorods.

[0051] S2. The prepared BiVO4 nanorods were ultrasonically cleaned in ethanol, acetone and water in sequence. Then, the electrochemical deposition method was used, with 0.05M ferric chloride, 0.05M potassium fluoride, 0.1M potassium chloride and 1M hydrogen peroxide solution as electrolyte, BiVO4 nanorods, Pt wires and Ag / AgCl as working electrodes, counter electrodes and reference electrodes respectively, and 15 cycles of electroplating were performed at a bias voltage of -0.15V to 0.5V vs. Ag / AgCl to deposit FeOOH on BiVO4 nanorods to obtain BiVO4 / Fe3OOH; then the above electrode sheets were annealed at 650℃ in an oxygen atmosphere for 2h; finally, they were rinsed in pure water to obtain heterojunction catalytic materials.

[0052] The heterojunction catalytic material of Example 2 was used for photoelectrolysis of water. The prepared heterojunction catalytic material was made into a photoelectrode. The photoelectrochemical test was carried out using an electrochemical workstation, as follows: 0.5 mol / L Na2PO4 (PH≈9) solution was used as the electrolyte, the prepared photoelectrode was used as the anode, Ag / AgCl was used as the reference electrode, Pt wire was used as the cathode, and a 300 W Xe lamp (light intensity ≈100 mW / cm 2 ) as the light source, and the photocurrent density-bias curve was obtained. Linear scanning curve of heterojunction catalytic material When the photoelectrode is biased at 1.2V vs. RHE, the photocurrent density is 0.21mA / cm 2 .

[0053] Example 3

[0054] This example provides a heterojunction catalytic material, comprising a conductive substrate, BiVO4 nanorods and Fe2O3; the BiVO4 nanorods are located on the surface of the substrate; Fe2O3 and the BiVO4 nanorods form a heterojunction; Fe2O3 is distributed on the BiVO4 nanorods, wherein the particle size of the BiVO4 nanorods is about 200nm, and the particle size of the heterojunction is about 300nm. The preparation method thereof comprises the following steps:

[0055] Substrate selection: FTO conductive glass (square resistance <15Ω) is used.

[0056] S1. Electrochemical deposition method was used, with 4 mM bismuth nitrate solution, 0.4 M potassium iodide and 0.2 M benzoquinone solution as electrolyte, FTO, Pt wire and Ag / AgCl as working electrode, counter electrode and reference electrode respectively, and BiOI was deposited on FTO for 400 s at a bias of -0.12 V vs. Ag / AgCl to obtain BiOI; then the above electrode sheets were immersed in 0.2 M vanadium acetylacetonate solution for 1 min, and annealed at 450 ° C in oxygen atmosphere for 2 h; finally, they were immersed in 1 M NaOH solution for 30 min to remove V2O5 to obtain BiVO4 nanorods.

[0057] S2. The prepared BiVO4 nanorods were ultrasonically cleaned in ethanol, acetone and water in sequence. Then, the electrochemical deposition method was used, with 0.05M ferric chloride, 0.05M potassium fluoride, 0.1M potassium chloride and 1M hydrogen peroxide solution as electrolyte, BiVO4 nanorods, Pt wires and Ag / AgCl as working electrodes, counter electrodes and reference electrodes respectively, and 15 cycles of electroplating were performed at a bias voltage of -0.20V to 0.5V vs. Ag / AgCl to deposit FeOOH on BiVO4 nanorods to obtain BiVO4 / Fe3OOH; then the above electrode sheets were annealed at 650°C in an oxygen atmosphere for 2h; finally, they were rinsed in pure water to obtain heterojunction catalytic materials.

[0058] The heterojunction catalytic material prepared in Example 3 was used for photoelectrolysis of water. The prepared heterojunction catalytic material was made into a photoelectrode. The photoelectrochemical test was carried out using an electrochemical workstation, as follows: 0.5 mol / L Na2PO4 (PH≈9) solution was used as the electrolyte, the prepared photoelectrode was used as the anode, Ag / AgCl was used as the reference electrode, Pt wire was used as the cathode, and a 300 W Xe lamp (light intensity ~100 mW / cm 2 ) as the light source, and the photocurrent density-bias curve was obtained. When the photoelectrode was biased at 1.2V vs. RHE, the photocurrent density was 0.15mA / cm 2 .

[0059] Comparative Example 1

[0060] Comparative Example 1 provides a catalytic material, and the preparation method thereof is as follows:

[0061] Substrate selection: FTO conductive glass (square resistance <15Ω) is used.

[0062] The electrochemical deposition method was adopted, with 4mM bismuth nitrate solution, 0.4M potassium iodide and 0.2M benzoquinone solution as electrolyte, FTO conductive glass, Pt wire and Ag / AgCl as working electrode, counter electrode and reference electrode respectively. BiOI was deposited on FTO by electrodeposition for 400s under a bias of -0.12V vs.Ag / AgCl to obtain BiOI; then it was immersed in 0.2M vanadium acetylacetonate solution for 1min, annealed at 450℃ in oxygen atmosphere for 2h; finally, it was immersed in 1M NaOH solution for 30min to remove V2O5 to obtain BiVO4 nanorods.

[0063] The BiVO4 nanorods of Comparative Example 1 were used for photoelectrolysis of water. The prepared heterojunction catalytic material was made into a photoelectrode. The photoelectrochemical test was carried out using an electrochemical workstation, as follows: 0.5 mol / L Na2PO4 (PH≈9) solution was used as the electrolyte, the prepared photoelectrode was used as the anode, Ag / AgCl was used as the reference electrode, Pt wire was used as the cathode, and a 300 W Xe lamp (light intensity ~100 mW / cm 2 ) as the light source, and the photocurrent density-bias curve was obtained. When the photoelectrode was biased at 1.2V vs. RHE, the photocurrent density was 0.14mA / cm 2 .

[0064] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.

Claims

1. A heterojunction catalytic material, characterized in that: The invention comprises a conductive substrate, BiVO4 nanorods and Fe2O3; the BiVO4 nanorods are located on the surface of the substrate; the Fe2O3 and the BiVO4 nanorods form a heterojunction; and the Fe2O3 is distributed on the BiVO4 nanorods.

2. The heterojunction catalytic material according to claim 1, characterized in that: The particle size of the BiVO4 nanorods is 150-300 nm.

3. The heterojunction catalytic material according to claim 1 or 2, characterized in that: The particle size of the heterojunction is 250-400 nm.

4. A method for preparing the heterojunction catalytic material according to any one of claims 1 to 3, characterized in that: The steps include: S1, using bismuth salt solution, potassium iodide solution and benzoquinone solution as electrolyte I, using conductive substrate as working electrode, and using electrochemical method to deposit I; mixing the working electrode and vanadium acetylacetonate solution and annealing I to obtain BiVO4 nanorod electrode; S2. Using a mixed solution of potassium chloride solution, potassium fluoride solution, ferric chloride solution and hydrogen peroxide solution as electrolyte II, using the BiVO4 nanorod electrode in step S1 as the working electrode, electrochemically depositing II and annealing II to obtain a heterojunction catalytic material.

5. The method for preparing a heterojunction catalytic material according to claim 4, characterized in that: The temperature of the annealing I is 400-700°C.

6. The method for preparing a heterojunction catalytic material according to claim 4, characterized in that: The temperature of the annealing II is 550-750°C.

7. The method for preparing a heterojunction catalytic material according to claim 4, characterized in that: In step S1, the concentration of the bismuth salt solution is 3-5 mM, the concentration of the potassium iodide solution is 0.3-0.6 M, and the concentration of the benzoquinone solution is 0.1-0.4 M.

8. The method for preparing a heterojunction catalytic material according to claim 4, characterized in that: In step S2, the concentration of the potassium chloride solution is 0.05-0.15M, the concentration of the potassium fluoride solution is 0.02-0.07M, the concentration of the ferric chloride solution is 0.02-0.06M, and the concentration of the hydrogen peroxide solution is 0.5-1.5M.

9. The method for preparing a heterojunction catalytic material according to claim 4, characterized in that: The voltage of the deposition I is -0.12 to -0.1 V vs. Ag / AgCl; Preferably, the voltage of the deposition II is -2.0V to 0.5V vs. Ag / AgCl.

10. Use of the heterojunction catalytic material according to any one of claims 1 to 3 in a photoelectrocatalytic water decomposition system.

Citation Information

Patent Citations

  • Visible-light catalytic film with dual oxygen-assisted catalytic layers and preparation method and application thereof

    CN105642291A